Habilidades sociales y dependencia emocional en estudiantes de una facultad de una Universidad de Ambato – Ecuador - Sandoval Villalba, Juan Francisco (2021)
The purpose of research was to determine the relationship between social skills and emotional dependence in 260 students from a faculty at a university in Ambato – Ecuador, which is one of the most representative universities of center of Ecuador and Ambato City. This research had a non-experimental approach, cross-sectional prospective observational and had a correlational descriptive design, with a quantitative approach. There was used Goldstein’s Social Skills Checklist and Lemos & Londoño’s Emotional Dependence Questionnaire, both adapted and validated through a pilot test, where in the case of the first instrument evidence of reliability was found (α = .955) and evidence of validity by internal structure through a six-factor model (49.43 % of variance), while in the case of the second instrument, evidence of reliability was found (α = .948) and evidence of validity by the internal structure of a general one-factor model (48.08 % of variance). The results indicated a low negative relationship between social skills and emotional dependency, without being significant. Likewise, there was determined that the relationship between emotional dependence and social skills areas was not statistically significant, except with alternative skills for aggression and stress coping skills. Also, there were found statistically significant differences in social skills and social skills’ areas in function of grades, and of same way, when comparing the emotional dependence.